Pathogenic Variability within Indian Alternaria brassicae Isolates Using Seed, Cotyledon and Leaf of Brassica Species. Issue 4 (April 2017) - Meena, Prabhu Dayal; Gupta, Riteka; Meena, Hari Singh; Sharma, Pankaj; Jambhulkar, Sanjay
Abstract: Thirty Alternaria brassicae (Berk.) Sacc. isolates from diverse geographical locations of India were studied for pathogenic variability on seed, cotyledon and true leaves of Brassica species. Seed germination was reduced maximum by isolate BAB‐39 in Brassica juncea cultivar Varuna (22.1%), Brassica rapa var. Toria cultivar PT‐303 (12%), Brassica carinata cultivar Kiran (12%), Brassica napus cultivar GSL‐1 (11%) and tolerant source of B. juncea genotype PHR‐2 (7%), although least by isolate BAB‐49. Maximum lesion size on leaf was recorded in B. juncea cultivar Rohini (11.2, 16.5 and 16.8 mm) with isolates BAB‐09 (Pantnagar), BAB‐19 (Bharatpur) and BAB‐39 (Kangra), respectively, and categorized as highly virulent, while minimum lesion size of 3.2, 3.7 and 3.8 mm was observed with isolates BAB‐47 (Tonk), BAB 49 (Jobner) and BAB 04 (Kamroop), respectively, considered the weak isolates. On B. alba, BAB‐09, BAB‐19 and BAB‐39 isolates caused maximum lesion size of 3.7, 3.8 and 3.9 mm, respectively, even though it showed maximum tolerance. In both seed and cotyledon inoculation method, the per cent Alternaria blight severity above 80% was observed with isolate of BAB‐39 (91.5%), BAB‐19 (89.0%), BAB‐09 (85.5%) and least in isolate BAB‐49 (34.0%). Brassica seed, cotyledon and leaf showed the similar positive response for categorizing A . brassicae isolates as virulent and avirulent. This information could be used to the development and assessment of resistant brassica germplasm, especially with A. brassicae populations exhibiting increased virulence.